ISRAEL’S ATTACK ON PALESTINE : BETWEEN GENOCIDE AND CONFLICT - Nurul Fathoro; Zihan Ali Hakim, Syamsu Rijal, Sona Fathurohman, Yayat Maulana, Bambang Yuniarto (International Journal Of Humanities, Social Sciences And Business (INJOSS), 2024)
Israel's attack on Palestine is the most phenomenal issue in the last few weeks. However, the question is being asked by a number of parties whether this attack constitutes genocide or conflict. Therefore, this research aims to analyze Israel's attacks on Palestine in the category of Genocide or Conflict. This research is qualitative research with a descriptive approach. The data used in this research is secondary data obtained from scientific articles, books, websites and a number of other reliable references. The research results show that Genosdia has 5 more concrete limitations, Israel's attack on Palestine is considered genocide because it fulfills these 5 categories of impacts. And this attack must be stopped immediately, either through diplomacy, a ceasefire, or even militarization